Strategi Adaptasi Warga terhadap Kondisi Sosial Fisik dan Kesehatan di Lingkungan Padat Rusun 26 Ilir Palembang - Penyta Purnama Arta Lestari; Nanda Riski Agustin; Chik Nurul Azura Norman; Yenis Alda; Rangga Pratama (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Rapid urbanization in Indonesia, particularly in medium-sized cities such as Palembang, has significantly increased the demand for vertical housing for low-income communities. However, a critical gap persists between infrastructure-oriented housing policies and the sociological realities of residents’ adaptation in dense living environments. This study aims to analyze residents’ adaptation strategies across social, physical, and health dimensions in high-density housing, with a specific focus on Rusun 26 Ilir Palembang.This research employs a Systematic Literature Review (SLR) approach following the PRISMA guidelines. Literature was systematically retrieved from Scopus, ScienceDirect, PubMed, Google Scholar, and Garuda databases, resulting in 25 selected articles published between 2020 and 2026.The findings reveal that social adaptation is primarily driven by community cohesion and informal support networks, strongly influenced by local values such as mutual cooperation (gotong royong). Physical adaptation is reflected in interior modifications and the use of multifunctional spaces as responses to spatial constraints. Meanwhile, health adaptation involves collective hygienic practices aimed at mitigating disease risks associated with high-density living conditions. The novelty of this study lies in the integration of these three adaptation dimensions within the context of vertical housing in a medium-sized city. The policy implications highlight the importance of designing housing that is responsive to socio-cultural dynamics and spatial flexibility to ensure sustainable living conditions for residents.